RISK OF HUMIDITY, TEMPERATURE, AIR GERM RATE, OCCUPANCY DENSITY, AND FAMILY MEMBERS WHO SMOKE ON THE INCIDENCE OF PNEUMONIA IN TODDLERS: META-ANALYSIS - Dwiani, Errisa (VISIKES, 2024)
Pneumonia is an acute respiratory disease that affects the human lungs. According to the World Health Organization (WHO), pneumonia accounted for about 14% of deaths in children worldwide in 2019. In 2018, Basic Health Research (Riskesdas) data stated that the incidence rate in Indonesia was around 2.1%, with the highest incidence rate at 12 to 23 months of age. Children with compromised immune systems may experience recurrent pneumonia or have difficulty coping effectively with the disease. This study analyzes the association between physical environmental risk factors, humidity, temperature, air germ count, occupancy density, and family members smoking inside the house with the incidence of pneumonia among under-fives in Indonesia from 2013-2023. This literature review used a quantitative meta-analysis method by combining 36 articles that met the criteria. The results of the meta-analysis showed that the variable of air humidity in the house was the most influential variable with a risk value of 4.854 times compared to other variables. The conclusion is the families can pay more attention to indoor air humidity in the house which is a major variable in the occurrence of pneumonia, such as increasing natural lighting, modifying the physical building, and using aids to reduce air humidity.